2017
DOI: 10.1128/aac.02015-16
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Observational Study of Ceftaroline Fosamil for Methicillin-Resistant Staphylococcus aureus Bloodstream Infections

Abstract: Novel therapies for methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infection (BSI) are needed in the setting of reduced antibiotic susceptibilities and therapeutic failure. Ceftaroline is a cephalosporin antibiotic with MRSA activity. Although not FDA approved for MRSA BSI, ceftaroline has generated much interest as a potential treatment option. However, detailed descriptions of its use in this setting remain limited. To address this, we conducted a retrospective, multicenter, observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 38 publications
1
60
0
5
Order By: Relevance
“…Zasowski and colleagues conducted a retrospective, multicenter, observational study of adult patients who received ceftaroline for ≥72 hours for MRSA bloodstream infections in three non-VHA hospitals in Michigan and Florida [8]. Compared to our study, the patient population in Zasowski’s study had more females (3% vs. 44%), less diabetes mellitus (56% vs. 37%), more hemodialysis (2% vs. 21%), lower Charlson scores (median score of 6 vs. 3), and were about the same age (61 vs. 59 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zasowski and colleagues conducted a retrospective, multicenter, observational study of adult patients who received ceftaroline for ≥72 hours for MRSA bloodstream infections in three non-VHA hospitals in Michigan and Florida [8]. Compared to our study, the patient population in Zasowski’s study had more females (3% vs. 44%), less diabetes mellitus (56% vs. 37%), more hemodialysis (2% vs. 21%), lower Charlson scores (median score of 6 vs. 3), and were about the same age (61 vs. 59 years).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 88% achieved clinical success and 92% survived the infection. Finally, Zasowski and colleagues studied 211 patients who received ceftaroline for MRSA bloodstream infections and found that 68% achieved clinical success [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Notable from this publication was the every 8‐hour dosing strategy employed resulting in effective bacterial eradication from the bloodstream. In vitro data corroborate an every 8‐hour dosing strategy which optimizes the pharmacokinetic/pharmacodynamics of ceftaroline; however, additional clinical experience with standard and high‐dose has also been associated with clinical success …”
Section: Resultsmentioning
confidence: 73%
“…In conjunction with in vitro data, the reliable activity against MRSA makes ceftaroline a viable option as a part of most salvage regimens for deep-seated infections such as endocarditis or where previous exposure to vancomycin or daptomycin failed to result in bloodstream sterilization. 56 As previously mentioned, combination therapy with either vancomycin or daptomycin has been described; however, ceftaroline monotherapy has also been used as salvage (available in vivo evidence shown in Table 3 resulting in a median time to blood sterilization of 1.5 days. Noted overall success was 31%; however, the study defined success as no clinical or microbiological recurrence at least 6 weeks after completion.…”
Section: Ceftarolinementioning
confidence: 99%
“…L'arrivée des céphalosporines dites « de 5 e généra-tion » (ceftaroline fosamil et ceftobiprole médocaril) constitue une véritable révolution puisque nous disposons, pour la première fois dans l'histoire de l'antibiothérapie, de β-lactamines actives sur les SARM, du fait de leur affinité conservé sur la PLP2a. Pour autant, les indications de ces molécules restent à préciser, d'autant qu'elles sont actuellement majoritairement utilisées en seconde ligne dans des bactériémies à SARM [3]. Pourtant, leur très bon profil de tolérance (celui des β-lactamines) et leur effet bactéricide rapide associé à un spectre large incluant des entérobactéries devraient en faire de très sérieux concurrents aux glyco-/lipopeptides, y compris dans le traitement probabiliste lorsque le risque de SARM est jugé élevé.…”
unclassified